UPDATED ASSESSMENT AND MANAGEMENT STUDY OF CERVICAL FACTOR INFERTILITY - Valencia Madera, Iván (2015)
The cervical spermatozoon migration mechanism plays a very important role in the human reproduction process. Its participation in the spermatozoon transportation as well as the cervical mucus functions are of great relevance in infertility. Rarely, the cervical factor is diagnosed as the only cause for infertility, since in most cases it only represents a relative obstacle. Its incidence is estimated between 5% and 10%. Frequently, the cervical factor may be one of the infertility components within the multifactorial etiology and it may strengthen other subfertility factors: seminal deficiency and ovulatory alterations.